1988
DOI: 10.1128/jb.170.8.3384-3389.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molybdenum and tungsten on synthesis and composition of formate dehydrogenase in Methanobacterium formicicum

Abstract: The influence of iodium molybdate amg sodium tate on fomate dehydave ity was stud in H2-C02-grw cues of Mathwobactenum fornicicur. Depletion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
4
44
0
Order By: Relevance
“…This has been shown, for example, for nitrogenas¢ from A:atabacter vinelandU [12], nitrate reductas¢ from plants [13], hepatic sulphit= oxidase [14], and formate dehydrog=nase from Methanabaeterium fomzt¢icum [15]. Rest activity of the enzymes can be attributed to small amounts of' molybdenum still pr¢s=nt.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown, for example, for nitrogenas¢ from A:atabacter vinelandU [12], nitrate reductas¢ from plants [13], hepatic sulphit= oxidase [14], and formate dehydrog=nase from Methanabaeterium fomzt¢icum [15]. Rest activity of the enzymes can be attributed to small amounts of' molybdenum still pr¢s=nt.…”
Section: Discussionmentioning
confidence: 99%
“…in Methylobacterium extorquens (Laukel et al, 2003) or in R. eutropha (Cramm, 2009). In various studies it was shown that the interchange of molybdenum and tungsten led to inactive enzymes which can be exploited to identify whether the enzyme of interest is molybdenumor tungsten-dependent (May et al, 1988;McMaster & Enemark, 1998). However, for the N-formylmethanofuran dehydrogenases from Methanobacterium thermoautotrophicum and Methanobacterium wolfeii the interchange of molybdenum and tungsten yields enzymes with comparable activities (Johnson et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The stimulating eVect of both the elements was found to be related to either the FDH levels in methanogens growing on formate, such as M. formicicum and Methanococcus vannielii (Jones and Stadtman 1981;May et al 1988), or to the FMDH level in methanogens growing on H 2 /CO 2 such as Methanothermobacter wolfei and Methanothermobacter marburgensis (Bertram et al 1994;Hochheimer et al 1998). Growth of M. formicicum and M. vannielii was not aVected by Mo or W when H 2 /CO 2 was the substrate instead of formate, as FDH is not required for autotrophic growth (Jones and Stadtman 1981;May et al 1988). Similar to these two methanogens, M. hungatei grows on both H 2 /CO 2 and formate.…”
Section: Evects Of W and Mo On The Growth Of M Hungateimentioning
confidence: 99%
“…Since the chemical and catalytic properties of these two metals are very similar, some enzymes contain either Mo or W, and some microorganisms even contain analogues of enzymes containing either W or Mo, depending on the growth conditions (Bertram et al 1994;Hochheimer et al 1998;Stewart et al 2000;Brondino et al 2004). However, most microorganisms just possess one type of enzyme, in which the W and Mo can not eVectively replace each other (Jones and Stadtman 1977;Van Bruggen et al 1986;Zindel et al 1988;Afshar et al 1998), and in some cases, they even have antagonistic eVects (Ljungdahl and Andreesen 1978;Zellner and Winter 1987;May et al 1988).…”
Section: Introductionmentioning
confidence: 99%